Tingkat Kemudahan dan Manfaat pada Penggunaan Layanan Go-Pay bagi Minat Pengguna di Indonesia - Friti Anifa; Anisa Anisa; Nailatul Fadhila; Ida Farida Adi Prawira (Organum: Jurnal Saintifik Manajemen dan Akuntansi, 2020)
The development of financial technology in Indonesia is followed by innovation, namely, the presence of E-Money. Go-Pay is a form of E-Money in Indonesia which is a mobile payment service found on the Go-Jek platform. This study provided a summary graphic representation of the theory-consistent evidence about the causes and effects of user interests of Go-Pay system in Indonesia. Some of the conveniences and benefits obtained from services such as top-up, payments, and fund transfers. The method used in this study is the type of library research. Data collection techniques used are qualitative data collection using existing data sources, that is, using data reduction to then concludes with logic, aesthetics, and ethics. Based on research that had been done, it could be concluded that the conveniences and benefits felt by consumers significantly affected their demand for using Go-Pay services. The implications of this research for science are as consideration for Go-Jek companies to increase the conveniences and benefits in Go-Pay payments, which implies increasing Go-Jek demand.